A comparative evaluation of autokeratorefractometry and keratotopography in patients with cicatricial corneal astigmatism - V. V. Neroev; E. V. Chentsova; D. S. Belyaev; A. V. Penkina (Российский офтальмологический журнал)
Purpose: to compare the data of autokeratorefractometry (AKR) and keratotopography (KT) of patients with eye trauma consequences and cicatricial corneal astigmatism. Material and Methods. 75 patients (75 eyes) aged 18 to 70 (averagely 36.9±13.9 years) with this pathology were examined for the dependence of astigmatism value on the distance between the nearest point of the scar and the optical center of the cornea. The cornea was divided into 3 zones: the central zone covering the area within a radius of 1.5 mm from the optical center, the paracentral zone with the radius between 1.6 and 3.0 mm from the optical center, and the peripheral zone starting at 3.1 mm from the optical center. Results. The best corrected visual acuity (BCVA) obtained using CT (0.79±0.13) in patients with paracentral location of the non-vascularized corneal scar was higher than that of patients who received AKR correction (0.73±0.16). Conclusions. The use of CT data in this group of patients significantly increases the accuracy of BCVA measurement, which, in turn, can affect the choice of the treatment plan. In the case of vascularized scars of the cornea of any localization, CT data will not be significantly more informative then AKR data as far as subjective correction choice is concerned // Russian Ophthalmological Journal, 2016; 3: 54-9. doi: 10.21516/2072-0076-2016-9-3-61-65.